2015
DOI: 10.1039/c5ra12941a
|View full text |Cite
|
Sign up to set email alerts
|

Novel nanocomposite membranes based on blended sulfonated poly(ether ether ketone)/poly(vinyl alcohol) containing sulfonated graphene oxide/Fe3O4 nanosheets for DMFC applications

Abstract: In this study, the Sulfonated graphene oxide (SGO)/Fe 3 O 4 nanosheets were synthesized by hydrothermal method and incorporated into blend sulfonated poly(ether ether ketone) (SPEEK)/poly(vinyl alchole) (PVA) matrix with different weight percent of (SGO)/Fe 3 O 4 nanosheets. The performances of prepared membranes were investigated by water uptake, membrane swelling, mechanical and thermal stability, proton conductivity, methanol permeability and DMFC test. It was found that the water uptake and tensile strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 53 publications
(100 reference statements)
2
51
0
Order By: Relevance
“…Again the existence of Fe 3 O 4 into the polymer matrix is a problem that facilitates the oxidative degradation of PEM when combined with hydroxyl (OHc) and hydroperoxyl (OOHc) radicals formed in cathode during PEMFC operation. Recently, Beydaghi et al 9 reported that the addition of 5 wt% Fe 3 O 4 -SGO could increase the durability of SPEEK/PVA blend signicantly. During 120 h of operation, the fuel cell equipped with Fe 3 O 4 -SGO/SPEEK/PVA membrane showed a OCV reduction of 0.…”
Section: 32mentioning
confidence: 99%
See 1 more Smart Citation
“…Again the existence of Fe 3 O 4 into the polymer matrix is a problem that facilitates the oxidative degradation of PEM when combined with hydroxyl (OHc) and hydroperoxyl (OOHc) radicals formed in cathode during PEMFC operation. Recently, Beydaghi et al 9 reported that the addition of 5 wt% Fe 3 O 4 -SGO could increase the durability of SPEEK/PVA blend signicantly. During 120 h of operation, the fuel cell equipped with Fe 3 O 4 -SGO/SPEEK/PVA membrane showed a OCV reduction of 0.…”
Section: 32mentioning
confidence: 99%
“…1,9 Besides, Naon membrane exhibits high hydrogen permeability denoted to as high hydrogen crossover from the anode to cathode through PEM as a result of concentration gradient. 10,11 Accordingly, researchers are developing modied PFSA membranes or designing alternative PEMs.…”
Section: -4mentioning
confidence: 99%
“…However, the water uptake decreased when the content of CeO 2 is more than 1 wt. %, probably due to the aggregation of oxide filler in the composite membrane [27]. Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…However, inadequate kinetics of methanol oxidation reaction in the anode, methanol crossover through the membranes, and poisoning effects of CO intermediates on the catalyst surface are three main challenges in the use of DMFC technology . The PEM is the crucial component in DMFCs that play an important role in fuel cell performance via an increase in proton conductivity as well as a barrier effect on methanol permeability . Additionally, the polymeric membrane should have desired properties such as suitable thermal, mechanical, and chemical stability; low cost; and easy film forming .…”
Section: Introductionmentioning
confidence: 99%